NON-PERFORMING ASSETS IN INDIAN BANKING SECTOR – A STUDY OF LITERATURE REVIEW - Pandey, Sachin Kumar; Srivastava, Pradeep Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A key driver of India’s economic growth has been the banking sector. While the rest of the world was scrambling to recover from a financial meltdown, the Indian banking sector had amazing development in the past few of years. As a result of the country’s successful economic growth and financial sector liberalisation throughout the last two decades, the banking industry in India has undergone significant changes. Nonperforming assets are becoming a problem for all types of banks, whether public and private. The COVID-19 epidemic has halted numerous economic operations worldwide, with the financial sector bearing the brunt of the impact; thus, none of those businesses can run economically. Nonperforming assets in India’s banking sector are the focus of this article’s literature study.